Combustion and Mechanical Properties of Polymer-Modified Cement Mortar at High Temperature - Hyung-Jun Kim; Won-Jun Park (Advances in Materials Science and Engineering)
Although polymer-modified cement mortar (PCM) has been extensively used as finishing and repairing material, it is necessary to understand its combustion properties and mechanical properties at high temperature. This study evaluated the combustion characteristics with varying experimental parameters such as polymer type, unit polymer content, polymer-cement ratio, and thickness of the specimen. This study also evaluated the compressive strength and elastic modulus of PCMs with focus on the effects of the type of polymer, unit polymer content, and polymer-cement ratio. As a result, the incombustibility of the PCM was in the following order: SBR < VVA < EVA. After heating end, the mass loss rate of the PCM was less than 30%, regardless of the polymer type, unit polymer content, and W/C. In heat release rate test, the higher the unit polymer content, the greater the total heat release, regardless of the difference in W/C. The PAE series showed excellent fire resistance in the temperature range of 200~400°C. PCMs with a unit polymer content of 5%, modified with EVA and PAE, showed outstanding compressive strength at 200~400°C. At elevated temperature, the modulus of elasticity of PCM declined with an increase in the unit polymer content, regardless of the polymer type.